Experimental Investigation on Performance of Vapor Compression Refrigeration System using Nanorefrigerant (R134a+Al2O3) with Evaporative Condenser - Raja, Niraj N.; Khanderao, Avinash D. (Asian Review of Mechanical Engineering, 2020)
In traditional refrigeration system the focus of researchers is always to improve its performance by reducing work of compression & enhancing the heat transfer rate in different heat exchangers and this can be achieved by adopting suitable technique. In this research work experiment is carried out on vapor compression refrigeration test rig using nanorefrigerant of R134a as base refrigerant and nanoparticles of aluminium oxide Al2O3 in different concentration so that variation in heat transfer rate can be observed. The different concentration of Al2O3 (gm/litre) in R134a were prepared, studied, and tested experimentally in VCR test rig. The test rig consists of evaporative condenser as conventional air-cooled condenser does not perform well in hot and dry climatic conditions. This evaporative air cooling offers desired heat rejection rate in condenser at high pressure and enhances system performance. The investigations show that nano refrigerant (R134a+ Al2O3 0.5gm/L Concentration & 50-60nm size) with evaporative condenser recorded the highest coefficient of performance among all other combination of nanorefrigerant. This indicates that nanorefrigerant can be safely experimented without any blockage or difficulty. The conventional VCR system operated with evaporative condenser without nanorefrigerant also shows improvement in performance compared to simple VCR with air cooled condenser. This system is suitable for hot and dry climate conditions.